(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Rabindranath Tagore was a universal personality. His genius was versatile. He was influenced by the Christian conception of the fatherhood of God and by Shakespeare, Goethe, and Wordsworth etc. But the roots of his intellectual creativism and emotional make-up lie in the Upanishads, in the poetry of kalidas, in the lyrics of Vaisnavas, in the mystic poems of Kabir and the religious atmosphere of the Brahmo Samaj. Tagore’s inspired poetry and prose becomes the literary vehicle of the regeneration of a fallen race. His songs and messages were like inspirations to social and political workers. Tagore was venerated as a seer of Indian freedom. Apart from his political and social thoughts his educational thoughts were also standing as a landmark in the educational system of India. He tried to give India an educational system which can meet the spiritual and natural needs of human beings. The objective of the paper is to analyses the educational thoughts of Tagore, his basic conception of education and its process. The paper is primarily based on secondary sources like the Books, Journals and Articles etc. The method used is historic-analytic method. Tagore was a great champion of education for international understanding.Rabindranath Tagore was a great philosopher, thinker, educationist, social activist and intellectual of 20th century. Tagore was a charismatic figure who had a rare great personality, exhibited multidimensional ideas and which has relevance in present era too. It represents important social and cultural changes of the present and rejects claims of classical social thinkers. He establishes a highly pluralistic and diverse view about the education. It represents important social and cultural changes of the present day and rejects the claims of classical social thinkers about the universalistic ideas about individuals; society and the world .It establish a highly pluralistic and diverse view about society with no grand narratives guiding its development. It suggests multiple quotations, cultural cross over and multicultural borrowing even in the field of education in general and society.